Book Review: G. Palanithurai and R. Ramesh, Integral Rural Development. (April 2017) - Kaur, Manjit
G. Palanithurai and R. Ramesh, Integral Rural Development . New Delhi: Concept Publishing Company Pvt. Ltd., 2015, 134 pp., ISBN-13: 978-93-5125-110-1.